Predator in the Pool? A Quantitative Evaluation of Non-indexed Open Access Journals in Aquaculture Research - Clements, Jeff C.; Daigle, Rémi M.; Froehlich, Halley E. (Frontiers in Marine Science, 2018)
Predatory open access (OA) journals can be defined as non-indexed journals that exploit the gold OA model for profit, often spamming academics with questionable e-mails promising rapid OA publication for a fee. In aquaculture – a rapidly growing and highly scrutinized field – the issue of such journals remains undocumented. We employed a quantitative approach to determine whether attributes of scientific quality and rigor differed between OA aquaculture journals not indexed in reputable databases and well-established, indexed journals. Using a Google search, we identified several non-indexed OA journals, gathered data on attributes of these journals and articles therein, and compared these data to well-established aquaculture journals indexed in quality-controlled bibliometric databases. We then used these data to determine if non-indexed journals were likely predatory OA journals and if they pose a potential threat to aquaculture research. On average, non-indexed OA journals published significantly fewer papers per year, had cheaper fees, and were more recently established than indexed journals. Articles in non-indexed journals were, on average, shorter, had fewer authors and references, and spent significantly less time in peer review than their indexed counterparts; the proportion of articles employing rigorous statistical analyses was also lower for non-indexed journals. Additionally, articles in non-indexed journals were more likely to be published by scientists from developing nations. Worryingly, non-indexed journals were more likely to be found using a Google search, and their articles superficially resembled those in indexed journals. These results suggest that the non-indexed aquaculture journals identified herein are likely predatory OA journals and pose a threat to aquaculture research and the public education and perception of aquaculture. There are several points of reference from this study that, in combination, may help scientists and the public more easily identify these possibly predatory journals typically were established after 2010, publishing <20 papers per year, had fees <$1000, and published articles <80 days after submission. Subsequently checking reputable and quality-controlled databases such as the Directory of Open Access Journals, Web of Science, Scopus, and Thompson Reuters can aid in confirming the legitimacy of non-indexed OA journals and can facilitate avoidance of these aquaculture journals.